The Effect of Investment, Liquidity, Profitability, Company Growth, And Company Size on Dividend Payout Ratio (Empirical Study of Consumption Goods Sector Companies Listed On the Indonesia Stock Exchange, 2017-2020) - Mesrawati Mesrawati; Elprika Girsang; Don Fera Binjori; Meli Samosir; Dina Arfianti Siregar (Budapest International Research and Critics University, 2023)
The dividend payout ratio is the ratio between the total dividends paid to shareholders and the company's net profit. This study aims to identify the factors that influence the Dividend Payout Ratio (DPR) in 17 companies listed on the Indonesia Stock Exchange. The data used in this study are annual financial reports from the period 2017 to 2020. Multiple linear regression analysis is used to analyze the data by testing the determinant coefficient, simultaneous test (f test), and partial test (t test). The variables studied include Investment, Liquidity, Profitability, Company Growth, Company Size, and Dividend Payout Ratio as the dependent variable. The results of the analysis show that the Profitability and Company Growth variables have a significant effect on the Dividend Payout Ratio, while the Investment, Liquidity, and Company Size variables have no significant effect on the Dividend Payout Ratio.